Accuracy of an infrared LED device to measure heart rate and energy expenditure during rest and exercise - Lee, C. M.; Gorelick, M.; Mendoza, A. (Journal of Sports Sciences, 2011)
The purpose of this study was to examine the accuracy of the ePulse Personal Fitness Assistant, a forearm-worn device that provides measures of heart rate and estimates energy expenditure. Forty-six participants engaged in 4-minute periods of standing, 2.0 mph walking, 3.5 mph walking, 4.5 mph jogging, and 6.0 mph running. Heart rate and energy expenditure were simultaneously recorded at 60-second intervals using the ePulse, an electrocardiogram (EKG), and indirect calorimetry. The heart rates obtained from the ePulse were highly correlated (intraclass correlation coefficients [ICCs] =0.85) with those from the EKG during all conditions. The typical errors progressively increased with increasing exercise intensity but were <5 bpm only during rest and 2.0 mph. Energy expenditure from the ePulse was poorly correlated with indirect calorimetry (ICCs: 0.01-0.36) and the typical errors for energy expenditure ranged from 0.69-2.97 kcal/min, progressively increasing with exercise intensity. These data suggest that the ePulse Personal Fitness Assistant is a valid device for monitoring heart rate at rest and low-intensity exercise, but becomes less accurate as exercise intensity increases. However, it does not appear to be a valid device to estimate energy expenditure during exercise.